Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Tembakau Kasturi Di Kecamatan Suela - Farhana Muhammad; Isfi Sholihah; Mirza Yuliana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the analysis of the factors that affect the income of kasturi tobacco farmers is Suela District. The type of research is descriptive quantitative, with a population of 3,093 and a sample of 72 Kasturi tobacco farmers. The technique chosen is the proposive sampling technique, the data collection technique is observation, documentation of assumption test and hypothesis testing, path analysis test, and to analyze the data using multiple linear regression using the SPSS 16 application. Then the results of the t test show that price significance value is 0,148 > 0,05 and the t count value is -1,464 < t table value 1,995 then it is rejected, the production cost is 0,00 < 0,05 with the t arithmetic value 9,391 > the t table value is 1,995 then Ha2 is accepted while the quality iss 0,397 > 0,05 and the t value is. -0,853 < t table value is 1,995, then Ha3 is rejected. So it can be concluded that price and quality have no significant effect on the income of tobacco farmers in Suela District, while production costs have a significant effect on the income of tobacco farmers is Suela District. Based on the results of the analysis of the simultaneous F test, namely the calculated F value > F table (31,392 > 2,74), then Ha4 is accepted. In addition, the value of sig 0,00 < 0,05 indicates that there is a significant effect of price, production costs and quality simultaneous effect on the income of tobacco farmers through quality as an intervining variable